FOREGN POLICY STRATEGY OF RUSSIA WITH RESPECT TO POST SOVIET COUNTRIES AS IMPLEMENTATION OF THE "NEW DOCTRINE OF LIMITED SOVEREIGNTY" - I. Lossovskyi (Стратегічна панорама, 2019)
The article analyzes the principles and practical implications of the implementation of the current foreign policy of the Russian Federation (RF) regarding the post-Soviet countries, first of all in relation to Ukraine, since the beginning of armed aggression against our state. On the basis of the analysis of the fundamental domestic military-political legal and regulatory documents of the RF, adopted in recent years, as well as the public statements of the Russian leadership, it was concluded that the new foreign policy strategy has been established by the Kremlin regime as well as corresponding to it its foreign policy doctrine. This doctrine could be called "the new doctrine of limited sovereignty", or "the doctrine of Putin," the main element of which is the restoration of the concept of "limited sovereignty", which, during the Cold War, was a major component of the so-called "Brezhnev Doctrine" – the Soviet Union foreign policy doctrine regarding the countries of the "peoples’ democracy". The preconditions are analyzed and the main provisions and characteristics of "Putin’s doctrine" are formulated. On the basis of existing documents of international law it is proved that Russia’s political and military activity in the last four and a half years on the territory of Ukraine is aggression against the latter, and the Russian Federation itself is an aggressor country and falls under the definition of the well-known western concept of "rogue states", which is widely used in contemporary international politics and political science. Issues of changes in the world order from the Westphalia system of international relations of 1648 and the successive seven its modifications that have taken place to date have also been considered. An important characteristic of the modifications of the Westphalia system mentioned in the article is the notion of "state sovereignty", which is also modified accordingly, depending on changes in the world order.